KEMAMPUAN SISWA KELAS VIIA SMP NEGERI 2 KOTA KUPANG DALAM MENULIS TEKS PROSEDUR BERDASARKAN HASIL PENGAMATAN VIDEO - Ajentro A. Nenabu; Labu Djuli; Samuel H. Nitbani (STKIP Subang, 2026)
The focus of this study is “How is the Ability of Grade VII A Students at SMP Negeri 2 Kupang City in Writing Procedure Texts Based on Video Observation Results?” The purpose of this study is to describe the ability of Grade VII A students at SMP Negeri 2 Kupang City in composing procedure texts through video observation. The theory of writing was used in this study because it assesses students’ ability to compose procedure texts. A qualitative descriptive methodology was applied in this research. The researcher selected procedure text material for this study. A procedure text is a text that explains the steps or methods that must be followed to achieve a particular goal. The results of the data analysis conducted on 28 students at SMP Negeri 2 Kupang City indicate that students were able to write procedure texts by paying attention to the structure and linguistic rules of procedure texts. This is proven by the percentage of students who achieved the minimum mastery criterion (KKM) score of 76 and above, totaling 22 students with a percentage of 78.6%, while 6 students did not achieve the KKM, with a percentage of 21.4%.